Diagnósticos das ocorrências ambientais registradas na Secretaria Municipal de Meio Ambiente, em Benjamin Constant, Amazonas, no período de 2017 a 2021 - Lopes, Rosiany da Silva (BRASIL, 2023)
The protection of nature has always been a challenge on the agenda of all governments, as the laws surrounding such issues are open and inconsistently applied. Taking this premise into account, infractions against the environment often occur without receiving the necessary attention, causing damage to the environment and the population. Therefore, it is important to carry out studies on issues related to the environment. Faced with the serious environmental problems observed in the municipalities of Alto Solimões, Amazonas, the idea of studying the environmental crimes that are registered at the Municipal Secretary of the Environment (SEMMA) and how they are treated. The present research derives from the UFAM Scientific Initiation Program and sought to investigate the different types of environmental crimes that occurred in the city of Benjamin Constant-AM in the period 2017 to 2021 registered at SEMA-BC. The records were obtained through documental research and exploratory field research. According to the data obtained, the results showed that in the years 2017 to 2021, more than 500 occurrences against nature were recorded, including noise pollution, inadequate disposal of solid waste, fires, open pits, animal husbandry, and others. With that, the present work sought to trace a profile of the author of such criminal action and carry out geographic mapping of the crime scenes, in addition to presenting the processes supervised and not supervised by SEMMA.